THE DEEP STRUCTURE AND PALEOGEODYNAMICS OF SIBERIA AND CENTRAL ASIA IN STUDIES OF THE INSTITUTE OF THE EARTH’S CRUST, SB RAS (2009–2013) - D. P. Gladkochub; E. Kh. Turutanov (Геодинамика и тектонофизика)
The deep structure and paleogeodynamics of the Siberian craton and the Central Asian folded belt are studied by two specialized laboratories of the Institute of the Earth’s Crust, SB RAS – the Laboratory of Complex Geophysics and the Laboratory of Paleogeodynamics. A variety of modern geophysical methods is applied. Surface wave tomography is focused on determination of 3D velocity structure of the upper mantle. Seismic, gravimetric and electrical surveys are aimed at studies of structures of the crust and the upper mantle. Geothermic parameters of the lithosphere in Central Asia are measured. In search for mineral resources, new geophysical prospecting technologies are developed. Quality paleogeodynamics reconstructions require a proper understanding of the structural evolution of the Siberian craton and the Central Asian folded belt. Researches in this scientific field are conducted by the Laboratory of Paleogeodynamics. Besides, the Laboratory studies new minerals and conditions of their formation. Some of the scientific research projects are jointly implemented by the two laboratories, and research results are regularly published in Russia and abroad.